Validation of an enzyme-linked inmunosorbent assay (ELISA) kit for the quantification of gliadins in medicines and cosmetics - Loría Gutiérrez, Arlene (2021)
Celiac disease is caused by intolerance to gluten and the only current treatment is a gluten-free diet. Gliadins are the alcohol-soluble proteins that make up the majority of gluten and are the ones that have the most harmful effect on patients with celiac disease. In recent years the issue of the presence of gluten in medicines and cosmetics, has become relevant since it is present in many excipients that are used as lubricants or absorbents, to provide mass or volume, give shape, color and consistency. The quantification of gliadins was carried out using the ELISA technique based on the R5 antibody, with a RIDASCREEN® Gliadin kit from R-Biopharm and a microplate ELISA spectrophotometer. To validate the immunological analytical method, the specificity, intermediate precision, relative accuracy and range were measured according to the USP 41 specifications for biologic assays. Recovery percentages of gliadins in positive control samples higher than 65 % were obtained. The relative standard deviation resulting from the amount of gliadins recovered to determine the intermediate precision of the kit was 7,6 %. Then, when determining the relative accuracy, an average absolute error value of 9,5 % was obtained. The range established to accurately and precisely analyze a sample was from 5 mg/kg to 80 mg/kg. The analytical method validated in this project meets performance characteristics such as specificity, intermediate precision, relative accuracy and range, suitable for the determination of gliadin content in drugs and cosmetics.